MENDORONG PERUBAHAN MINDSET DAN PERLINDUNGAN HAK CIPTA KARYA DIGITAL DALAM MENGAKSELERASI TRANSFORMASI DIGITAL UNTUK MENJADIKAN UMKM KOTA BANDUNG NAIK KELAS - Nurani, Nina; Hermina, Nurul; Oktari, Sari Dewi; Marinda, Vina Silviani; Budiawan, Andi (LPPM Universitas Bina Bangsa, 2024)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays an important role in the national economy, especially in creating jobs and increasing people's income. Based on this, the implementing team held training and counseling activities related to the theme